Welding gloves - Nik Abd Aziz, Nik Nuramalina; Masdan, Nursyahirah; Othman, Siti Amira (Penerbit UTHM, 2020)
There are many types of protective equipment at the workplace depending on the situation which one needs to be used since we know that workplace can create many hazards to our body parts. It is important to know when to use different types of gloves at the correct time while working where it can reduce the risk of any injuries and provide protection to the workers. It is said that gloves are one of the most important protective equipment since studies show that the ratio of injuries involving fingers or hand at workplace is about 1:4. Misusing the gloves or not wearing it at all will lead to injuries.